Accurate Flexible Temperature Sensor Based on Laser-Induced Graphene Material - Huang Kun; Liu Bin; Mostafa Orban; Qiu Donghai; Yang Hongbo (Shock and Vibration)
Body temperature is an essential physiological index reflecting human health. Accurate measurements of body temperature play a vital role in the diagnosis and treatment of diseases. In this paper, a temperature sensor manufactured by laser-induced graphene is introduced. This sensor has high measurement accuracy, simple preparation, and low production cost. The sensor is made of laser-induced graphene and is easier to fabricate and operate than traditional thermal resistance sensors. The sensor is of high accuracy, is easy to manufacture, and is of low cost. The sensor has high accuracy and is linear between 30°C and 40°C in the human body temperature ranges. Laser-induced graphene (LIG) sensor’s resistance value is correlated linearly with the temperature value, and compared with the infrared thermometer, the accuracy of the sensor is ±0.15°C while that of the infrared thermometer is ±0.30°C. The sensitivity of the LIG sensor is −0.04145%°C−1.